Evaluation of anti-lipoxygenase activity of Cassia fistula linn leaves using in vitro methods - Gopi, Anju; Jisho, Manju (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Numerous plants are claimed to possess anti-inflammatory phytoconstituents in folk medicine, however, one among them is Cassia fistula linn leaves. The tree is 6-9 m high with straight trunk and smooth bark. It is pale green when young and gets rough and dark when old. The leaves are 23-30cm long and have got 4-8 pairs of oblong leaflets. Due to lack of specific scientific reports regarding its use for its anti-lipoxygenase property, this particular plant was selected for this particular study with the aim to bring scientific evidence for its therapeutic use. Methods: The anti-lipoxygenase study as carried by using 5-lipoxygenase(5-LOX) assay and 12-lipoxygenase(12-LOX) assay. In both the methods, absorbance of various concentrations of the tests and the control solutions were measured at 234nm. Results: Preliminary phytochemical study showed the presence of flavonoids, glycosides, tannins and phenolics. It was found that both the 5-LOX and 12-LOX were inhibited by the extract with a 50% inhibitory concentration (IC50) of 6.23mg/ml obtained for the 5-LOX assay and an IC50 of 3.22mg/ml attained for the 12-LOX assay. Conclusions: The methanolic extract of the plant’s leaves showed anti-lipoxygenase activity similar to Indomethacin, thus ensuring that it could be used as an effective anti-inflammatory medicine.